The role of microRNAs in islet β‐cell development. (2nd November 2016) - Kaviani, Maryam; Azarpira, Negar; Karimi, Mohammad Hossein; Al‐Abdullah, Ismail
Abstract: Cell‐based therapies suggest novel treatments to overcome the complication of the current therapeutic approaches in diabetes mellitus type 1. Replacement of the destroyed pancreatic islet β‐cells by appropriate alternative cells needs an efficient approach to differentiate the cells into viable and functional insulin producing cells. Small non‐coding RNA molecules, microRNAs (miRNA), have critical roles in post‐transcriptional regulation of gene expression. Therefore, they can direct the cells toward β‐cell like cells and control islet β‐cell development. Previous reports showed the manipulation of the miRNA expression on islet β‐cell differentiation and regeneration. Likewise, the regulation of epithelial to mesenchymal transition by the miR‐30 family and the miR‐200 family may be a useful approach to conduct islet β‐cell development. Investigation of stem cells differentiation showed that the dynamic expression patterns of miR‐375 and miR‐7 are similar to developing human fetal pancreas while dynamic expression of miR‐146a and miR‐34a occurred during the differentiation. Moreover, miR‐342 and its both targets, FOXA2 and MAFB, are found in β‐cell differentiation and maturation. Because miRNAs can target specific transcription factors during islet β‐cell development and differentiation, they could be offerred as alternative regenerative treatment for diabetes mellitus. Considering that the application of these non‐coding RNAs remains limited in the literature, in this review article, we present an overview of the roles of miRNAs in the islet β‐cell development, focusing on the application of different miRNAs in the experimental protocols.